Risk assessment of heavy metal pollution in agricultural soil surrounding a typical pharmaceutical manufacturing complex - Su, Qu; Zhang, Xiaofang; Zhang, Yao; Sun, Gang; Li, Zheyong; Xiang, Luojing; Cai, Junxiong (Frontiers in Environmental Science, 2023)
The identification and effective control of pollution sources is essential because heavy metal pollution in agricultural soil is associated with food safety and public health. Industrial wastewater, waste gas, and residues generated from pharmaceutical manufacturing are important sources of heavy metal pollutants in soil, but the research of their risk for surrounding agricultural soil is inadequate. In this study, the typical pharmaceutical manufacturing complex and its surrounding farmland in Hubei Province, China was employed to systematically and comprehensively assess its environmental risk and source apportionment. The results revealed the potential risk of cadmium (Cd), lead (Pb), arsenic (As), and mercury (Hg) from pharmaceutical production for farmland soil around, and among these heavy metals, As and Cd were observed to have the higher pollution level. The accumulated Cd and As had contribution to a series of risks, including comprehensive pollution risk, geo-accumulation risk, potential ecological risk, and the carcinogenic and non-carcinogenic risk. Positive matrix factorization (PMF) source analysis combining with the geographic distribution of heavy metal surrounding pharmaceutical manufacturing confirmed that there were three main heavy metal pollution sources, including pharmaceutical wastewater, traffic, and agricultural chemicals, which had the 52.37%, 16.49%, and 31.14% contributions to the surrounding agricultural soil. The present study provided systematic strategies of environment risk assessment and source apportionment, and can be referred for casual analysis and prevention strategies for farmland soil surrounding pharmaceutical manufacturing complex.